Determination of potential volatile compounds in polyethylene terephthalate (PET) bottles and their short- and long-term migration into food simulants and soft drink. (15th December 2022) - Ozaki, Asako; Kishi, Eri; Ooshima, Tomoko; Kakutani, Naoya; Abe, Yutaka; Mutsuga, Motoh; Yamaguchi, Yukihiko; Yamano, Tetsuo
Highlights: A total of 6 volatile compounds were identified in virgin PET beverage bottles. To study these volatiles, a rapid and accurate method was developed using PT-GC–MS. The maximum migration of 2-methyl-1, 3-dioxolane was < 20 ng/mL after 2 y at 25 °C. Migration of 2-methyl-1, 3-dioxolane was also observed in commercially bottled water. Human exposure was estimated and was of low concern for the public health. Abstract: Head space (HS)-GC–MS was used to analyze possible migration of volatile compounds from polyethylene terephthalate (PET) bottles for soft drinks, and a total of six compounds were identified. Next, a rapid, simple, and accurate simultaneous method was established using purge-and-trap (PT)-GC–MS, to quantify their amounts in the liquid contents after short- and long-term storage in PET bottles. Starting with brand-new PET bottles, the maximum migration of 2-methyl-1, 3-dioxolane into distilled water and 50 % aqueous ethanol after 2 years at 25 °C were 2.3 and 19 ng/mL, respectively. In commercially available bottled mineral water sold inside and outside Japan, we were able to detect 2-methyl-1, 3-dioxolane in the same way. While nonanal was also detected in some products, 2-methyl-1, 3-dioxolane was confirmed as the main volatile compound. Finally, the human exposure to 2-methyl-1, 3-dioxolane was estimated based on the per capita intake of soft drinks in Japan and the migration amount in this study.